2011
DOI: 10.1002/art.30400
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, body weight, physical exercise, and risk of lower limb total joint replacement in a population‐based cohort of men

Abstract: Objective. To assess the associations of smoking, body weight, and physical activity with risk of undergoing total joint replacement (TJR) in a population-based cohort of men.Methods. A cohort study of 11,388 men that integrated clinical data with hospital morbidity data and mortality records was undertaken. The risk of undergoing TJR was modeled on baseline weight, height, comorbidity, socioeconomic status, years of smoking, and exercise in 3 separate age groups, using Cox proportional hazards regressions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 46 publications
(98 reference statements)
8
45
1
Order By: Relevance
“…This study suggested that the primary exposure of cigarette smoking was negatively associated with radiographic knee OA in the Chinese population, which was consistent with some previous researches [29,[40][41][42][43]. Two recent studies, including a large-sample prospective cohort study conducted by Mnatzaganian et al [40,41], considered total joint replacement (TJR) as a surrogate indicator of severe OA and demonstrated a strong inverse dose-response relationship between the duration of cigarette smoking and the risk of TJR. Another important largesample prospective cohort study conducted by Leung [29] reported a very strong dose-dependent association between the increased duration and dosage of cigarette smoking and the decreased risk of total knee replacement (TKR) among active smokers.…”
Section: Discussionsupporting
confidence: 90%
“…This study suggested that the primary exposure of cigarette smoking was negatively associated with radiographic knee OA in the Chinese population, which was consistent with some previous researches [29,[40][41][42][43]. Two recent studies, including a large-sample prospective cohort study conducted by Mnatzaganian et al [40,41], considered total joint replacement (TJR) as a surrogate indicator of severe OA and demonstrated a strong inverse dose-response relationship between the duration of cigarette smoking and the risk of TJR. Another important largesample prospective cohort study conducted by Leung [29] reported a very strong dose-dependent association between the increased duration and dosage of cigarette smoking and the decreased risk of total knee replacement (TKR) among active smokers.…”
Section: Discussionsupporting
confidence: 90%
“…Of the initially recruited 12,203 participants, 2,202 were eligible to participate in this study and were followed from baseline screening (1996e1999) until they experienced their first elective primary total hip or total knee replacement (TKR) or died or were right censored at the end of follow-up (March 2007) [9,10].…”
Section: Construction Of the Psmentioning
confidence: 99%
“…However, the majority of TJRs in this study were undertaken in the private hospital setting (78.5%). Those treated in the public system were more likely to be socioeconomically disadvantaged and smoked more years 5 , and therefore more likely to have waited longer for the surgery.…”
Section: Smoking and Osteoarthritismentioning
confidence: 99%
“…4,5 Headlines such as this, however, can disrupt tobacco control messages that are provided by public health organisations and government health departments to reduce the prevalence of smoking in the community.…”
Section: Smoking and Osteoarthritismentioning
confidence: 99%